2013
DOI: 10.1080/00224499.2012.763086
|View full text |Cite
|
Sign up to set email alerts
|

Women's Unprotected Sex Intentions: Roles of Sexual Victimization, Intoxication, and Partner Perception

Abstract: Sexually victimized women may make sexual decisions differently than non-victimized women. This study used an eroticized scenario and laboratory alcohol administration to investigate the roles of victimization history, intoxication, and relationship context in women’s perceptions of a male partner and their subsequent intentions for unprotected sex. A community sample of 436 women completed childhood sexual abuse (CSA) and adolescent/adult sexual assault (ASA) measures. After random assignment to an alcohol or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 49 publications
(52 reference statements)
2
39
1
Order By: Relevance
“…Although estimates vary across studies due to sample characteristics and survey methods, up to 80% of women report sexual victimization and up to 64% of men report sexual aggression (SA) perpetration since age 14 (Abbey, Parkhill, BeShears, Clinton-Sherrod, & Zawacki, 2006; Masters et al, 2013), which includes nonconsensual sexual contact as well as attempted and completed nonconsensual sexual intercourse. Because many of these sexual assaults involve alcohol consumption by the perpetrator, the victim, or both (Abbey, 2011; Testa, 2002), continued empirical investigation of alcohol-involved sexual assaults is essential.…”
mentioning
confidence: 99%
“…Although estimates vary across studies due to sample characteristics and survey methods, up to 80% of women report sexual victimization and up to 64% of men report sexual aggression (SA) perpetration since age 14 (Abbey, Parkhill, BeShears, Clinton-Sherrod, & Zawacki, 2006; Masters et al, 2013), which includes nonconsensual sexual contact as well as attempted and completed nonconsensual sexual intercourse. Because many of these sexual assaults involve alcohol consumption by the perpetrator, the victim, or both (Abbey, 2011; Testa, 2002), continued empirical investigation of alcohol-involved sexual assaults is essential.…”
mentioning
confidence: 99%
“…Extensive evidence has found that CSA women report inconsistent condom use, have more sexual partners, and are less able to attend to risk cues in a sexual situation (for a review, see Loeb et al, 2002). However, few studies have used experimental paradigms to examine in-the-moment sexual risk-taking, and only one study has examined the relationship between CSA and sexual abdication intentions (Masters et al, 2013). Despite higher rates of sexual risk among CSA women than in the general population, some studies find no differences between abused and non-abused women in sexual risk-taking (Loeb et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Only one experiment to date examined women’s sexual victimization history, alcohol intoxication, and sexual abdication. Masters et al (2013) found that alcohol increased sexual abdication directly and indirectly; CSA increased abdication indirectly via adult sexual assault and perceptions of the partner. Sexual abdication was positively associated with unprotected sex likelihood.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations